Multidisciplinary detective work prevent unnecessary and expensive lifelong treatment. Issue 5 (22nd April 2012) - Jarvis, S; Bowron, A; Powers, V; Pierre, G
Abstract : A 3-month old girl, patient A, was admitted to Bristol Royal Hospital for Children with severe respiratory problems. Following progressive muscle weakness she was transferred at 5 months of age to Paediatric Intensive Care for ventilation. She had persistent lactic acidosis and an abnormal urine organic acid analysis suggestive of mitochondrial dysfunction. At 6 months of age, sodium dichloroacetate (DCA) was started to treat her lactic acidosis. 7 weeks later, repeat organic acid analysis showed markedly increased succinylacetone and maleic acid, toxic metabolites of the tyrosine metabolic pathway. Succinylacetone is found in tyrosinaemia type I, but maleic acid has not been reported in a metabolic disorder. A review of earlier organic acid analyses identified previously undetected traces of maleic acid. It was proposed that patient A had an inherited deficiency of maleylacetoacetate isomerase (MAAI), an enzyme higher in the pathway. DCA inhibits MAAI and its addition may have lead to significant increases in maleic acid with secondary increases in succinylacetone. The DCA was stopped and nitisinone started to remove the toxic metabolites. However, no abnormality was found on sequencing the MAAI gene. During this period, maleic acid was detected in urine from a second patient in three separate samples. This abnormal finding disappeared 2 months later without treatment. On reviewing her drug history it was noticed that she had been prescribed domperidone, as a maleate salt. It was hypothesised that this contributed to the appearance of maleic acid in her urine, prompting a review of patient A's drug history. She had been receiving domperidone maleate from 4 to 6 months of age and amlodipine maleate, from 6 to 7 months. Maleate salts are used in several common drugs including domperidone, amlodipine and enalapril but urine maleic acid is a very rare finding. It was hypothesised that both patients may have a polymorphism in a drug metabolising enzyme causing slow metabolism of maleic acid. This caused small increases in maleic acid, but the addition of DCA in patient A impaired MAAI activity, resulting in marked increases. Nitisinone was stopped after 12 months, following these investigations, with no deterioration in clinical state, or return of maleic acid or succinylacetone, although markers of mitochondrial dysfunction persisted. Patient A has been further investigated but no firm diagnosis made. She remains ventilator dependent, awaiting a discharge package, on a 'metabolic cocktail' of vitamins. Organic acid abnormalities secondary to drugs are common. Clarification of the aetiology of these abnormalities is important to avoid unnecessary costly and invasive subsequent investigations and treatment. There were financial implications in this case: the cost of nitisinone treatment for patient A was £43 500 and the cost of biochemical monitoring was approximately £4000. The case highlights the importance of a full drug history when interpreting complex metabolic investigations and of the benefit of close working between the pharmacist and clinical biochemist.